Investigation of Hydro-Geochemical Characteristics of Groundwater In Port Harcourt City, Nigeria: Implication for Use and Vulnerability - HO Nwankwoala; GJ Udom (Journal of Applied Sciences and Environmental Management)
A hydrogeochemical evaluation of groundwater in Port Harcourt City, Southern Nigeria has been carried out. Thirty two (32) groundwater samples were analysed for their physical, chemical and microbiological properties. The average temperature of the groundwater samples is 29 oC, The water is slightly acidic with pH values between 4.28 – 7.72. Elevated Electrical Conductivity (EC) values in some coastal wells suggest possible pollution by seawater. The study also reveals saltwater contamination in the area as Chloride contents in some boreholes are up to 710.00mg/l. Besides of the major chemical compositions, ionic ratio (HCO3/Cl, Na/Ca, Ca/Cl, Mg/Cl and Ca/SO4) was used to delineate saline water intrusion. Iron and Manganese concentrations are above the World Health Organization guide value in majority of the boreholes studied, with maximum value up to 1.60mg/l in Abuloma area. Constituents of the heavy metals as shown in this study reveal that, in some locations, values are slightly higher than the permissible levels. Microbial analysis of the water samples to determine the presumptive coliform count of the water indicates the presence of coliform bacteria in majority of the analysed samples, indicating anthropogenic contamination of groundwater. The water is generally classified as soft and fresh based on its hardness and Total Dissolved Solids (TDS), which ranges from 2.50mg/l – 142mg/l and 2.60mg/l – 401mg/l, respectively. The analytical results present the abundance of the ions in the following order: Mg > Ca > Na > K = Cl > SO4 > HCO3 > NO3. Chloride is the dominant anion found in the groundwater of the study area. Piper trilinear diagram for the study area shows that there is a mixture of two types of water with variable concentrations of major ions. These are Ca – Mg –Cl – SO4 type and Na + K – Cl – SO4 type water. The second water type is also influenced by NO3. This means that groundwater in the area is mainly made up of mixtures of earth alkaline and alkaline metals and predominantly Cl- -SO4 2-water type. Most of the water samples are made up of mixtures of the two water types. The study provides the basic tool for sustainable groundwater management in the area in the context of quality assessment. @JASEM